An Impact of Education Marketing on Enrolment of Students at Private Management Colleges in Kathmandu - Pokhrel, Sagar; Tiwari, Ashish; Phuyal, Ram Kumar (Journal of Business and Social Sciences Research, 2018)
This paper attempts to examine the impact of different educational marketing activities undertaken by Kathmandu valley located selected private management colleges. The study has gone through the behaviour of BBA and MBA enrolled students who were recruited by the private management colleges (affiliated to both domestic and foreign universities in Nepal). The conceptual model adopted for this study consists with 7Ps of marketing mix developed by Kotler and Fox (1995) which is specially designed for educational institutions. Self-administered questionnaires were distributed to 342 students studying in 9 different colleges of Kathmandu valley in the year 2015, and the collected data was analyzed through descriptive statistics approaches. The analysis of the available information revealed that the most important influencing factor for admission at the BBA and MBA levels was recommendations made by the friends. However, the words of mouth i.e. family and relatives’ recommendations, colleges’ website and newspapers’ advertisements were also found to be effective. At the BBA level, lecturers, provision for extra-curricular activities, library and IT facilities were also of the high value for the enrolment whereas at the MBA level, profile of lecturers, teaching practices, possibilities of future employment opportunities and better placement were high on the agenda. We believe that the outcome of this study will be helpful for all private colleges, advertising agencies, and government educational agencies of Nepal to understand the psychology of students and to develop effective marketing strategies. It will further support to regulate those activities that best meet the interest of students and service providers to increase attraction among all the potential students in the private colleges. Journal of Business and Social Sciences Research, Vol. 1, Issue 1, pp. 22-36